Early symptoms of modernism in traditional Balinese painting began in Northern Bali / I Dewa Alit Dwija Putra and Sarena Abdullah - Dwija Putra, I Dewa Alit; Abdullah, Sarena (Universiti Teknologi MARA, Perak, 2020)
The history of significant changes in traditional Balinese art towards modern art took place in the 1930s in the village of Ubud, South Bali. Visual changes in Balinese art are unlike changes in modern art in the West or in Indonesian modern art. The visuals show a strong traditional style, although signs of modernity as this paper will argue, can be found. Modern Balinese art in Ubud in the 1930s actually started in North Bali in the 1870s. It was the role of two Dutchmen named Van der Tuuk and W.O.J. Nieuwenkamp, a linguist and academic artist, who contributed to the introduction of modern art to North Balinese artists. The interaction between the two Dutchmen and the local artists gave birth to arts that are slightly different from traditional arts in Bali. This paper will discuss the shift from traditional to modern painting done by Balinese artists in this early period that resulted in the transition of traditional to modern art through the changes in techniques and media; and themes and functions of these visuals. As such, this marks a shift from art that are no longer spiritual but lean more towards the profane.